Hygiene and Sanitation of Padang Restaurants in the Kalimanah Community Health Center Area, Purbalingga Regency - Hamidah, Siti; Aulia, Nuansa Dwika; Rudatiningtyas, Ulfa Fadilla; Heriyono, Muhamad (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
National data from the Central Bureau of Statistics and industry surveys indicate that Padang restaurants are among the most widely distributed traditional food businesses in Indonesia, operating across nearly all provinces and urban–peri-urban areas. Inadequate processing practices can precipitate foodborne disease. Environmental Health Inspections are therefore used to supervise food safety, ensure products are fit for consumption, and detect hazards along the processing chain. According to 2023 inspection standards, only 60.7% of food processing establishments nationally meet the required criteria. In Purbalingga Regency, just 186 of 1,460 restaurants are compliant. Within the Kalimanah Community Health Center (UPTD) catchment, 452 food processing places (TPPs) operate, many below standard. This study aimed to characterize food-processing practices in Padang restaurants in the Kalimanah UPTD area. A quantitative descriptive, cross-sectional design was employed. Thirty-three Padang restaurants were sampled; data were collected through observation and interview. Findings showed consistently high risk across several assessment domains. Of eight criteria evaluated, the cooked-food packaging area was classified as high risk in 100% of establishments. The external premises and the kitchen/food-storage areas were also high risk based on both mean and mode scores. These results underscore substantial food-safety vulnerabilities in Padang restaurants within the study area. Targeted follow-up supervision, training of food handlers, and corrective actions by owners are warranted to improve compliance with inspection standards and reduce the risk of foodborne illness.